STUDENT READING SKILL TRAINING THROUGH THE DEVELOPMENT OF MULTIMEDIA AS A LEARNING DEVICE - Ikhwani Ikhwani (BRIGHT VISION Journal of Language and Education, 2023)
This study aims to develop multimedia as a learning tool in training the reading skills of islamic elementary school (MI) students. This research uses a research and development (R&D) approach, through a Gall & Borg development study. This research is set in MIN 42 Pidie. The learning model is integrated with various learning tools (multimedia) including student and teacher books, as well as lesson plans (RPP). Based on the data obtained, it is known that multimedia integrated with the inquiry instructional model is effective in improving student learning outcomes rather than without using multimedia. It is proven through t-test statistical testing where tcount (9.98) is higher than ttable (2.00), means that multimedia integrated with the inquiry instructional model has a practical level with a score of 3.39 in the practical category without improvement.